Hegel's naturalism mind, nature, and the final ends of life - Pinkard, Terry P. (New York ; Oxford : Oxford University Press, 2012)
Terry Pinkard draws on Hegel's central works as well as his lectures on aesthetics, the history of philosophy, and the philosophy of history in this deeply informed and original exploration of Hegel's naturalism.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.